2018
DOI: 10.1002/jctb.5785
|View full text |Cite
|
Sign up to set email alerts
|

High purity fructose from inulin with heterogeneous catalysis – from batch to continuous operation

Abstract: BACKGROUND Inulin is a valuable source of high purity fructose. The conversion of inulin to fructose utilizing an advanced sulfonic ion‐exchange resin was previously investigated in detail in a batch reactor study, where a detailed mechanistic model for the reaction kinetics was demonstrated (J Chem Technol Biotechnol 2018;93:224–232). The same catalyst was employed in tailor‐made continuous fixed‐bed reactors in the current work in order to study the feasibility of continuous operation. RESULTS Two types of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…24,28 Based on literature and preliminary results obtained at ambient pressure, relatively high temperature and low pH are required in the hydrolysis of xylan compared to inulin, for example. [28][29][30] We selected 115 °C as the operating temperature in the screening as some of the catalysts have a maximum operating temperature of 120 °C. A pH of 0.75 was used to maintain a reasonable solid-liquid ratio.…”
Section: Resultsmentioning
confidence: 99%
“…24,28 Based on literature and preliminary results obtained at ambient pressure, relatively high temperature and low pH are required in the hydrolysis of xylan compared to inulin, for example. [28][29][30] We selected 115 °C as the operating temperature in the screening as some of the catalysts have a maximum operating temperature of 120 °C. A pH of 0.75 was used to maintain a reasonable solid-liquid ratio.…”
Section: Resultsmentioning
confidence: 99%
“…High‐fructose syrup (HFS) has increasingly solicited industrial importance over the years as an ingredient in food and pharmaceuticals. As it is 1.2 to 1.6 times sweeter than conventional sucrose, fructose is widely used in the food industry as a sweetener with flavour‐enhancing properties [ 1 ]. It also serves various non‐food applications and has been widely utilized for the production of bulk chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the dehydration of fructose has been extensively explored for the production of the important platform chemical, 5‐hydroxymethylfurfural, which can be utilized for the production of an array of chemical building blocks [ 2 ]. The conventional method for the commercial production of fructose is the isomerization of glucose, mediated by the enzyme isomerase [ 1 ]. However, the enzymatic isomerization of glucose produces an equimolar mixture of the two carbohydrates, which situates an economic constraint in the separation process.…”
Section: Introductionmentioning
confidence: 99%
“…studied the hydrolysis of cellobiose catalyzed by activated carbon and found that the weak acid sites were favorable for high selectivity of glucose, while strong acid groups were more accessible for the degradation reactions 12 . Besides carbon catalysts, ion‐exchange resins were also employed for hydrolysis reactions; 75% fructose yield was obtained with the multiple‐bed reactor catalyzed by sulfonic ion‐exchange 13 . Moreover, some metal oxides, such as TiO 2 ‐based catalysts 7 and ZSM‐5 zeolite, 14 were also investigated for polysaccharide hydrolysis.…”
Section: Introductionmentioning
confidence: 99%